DAMPAK PEMBIAYAAN MURABAHAH TERHADAP PENINGKATAN KESEJAHTERAAN NASABAH DI KOTA BOGOR - Shobri Shobri; Didin Hafidhuddin; Irfan Syauqi Beik (Kasaba, 2019)
This reseach aims to find effect of murabahah financing though well-being increasing at teacher around Bogor city. This reseach uses quantitative approach with correlation analysis as analityc tools. Findings this reseach; first, there are effect margin cost though costumer well-being. Second, financing period also has positive effect though costumer well-being. The conclution is murabahah financing on Islamic banking have effort to increase well-being especially teacher at Bogor city.